High-temperature air-oxidation of NiCoCrAlx medium-entropy alloys. (November 2021) - Kai, W.; Jiang, Z.Y.; Chen, G.T.; Lee, I.H.; Lin, H.J.; Hsieh, H.H.; Lin, W.T.; Kai, J.J.
Abstract: The oxidation behaviour of four NiCoCrAlx medium-entropy alloys (x = 0, 0.1, 0.3, or 0.5 mol.) was investigated in dry air at 600–900 °C. The oxidation kinetics of all the alloys followed the parabolic rate law at T> 700 °C, and the oxidation rates increased with an increase in temperature and a decrease in Al content. Discontinuous oxide granules were formed on all the alloys at 600 °C, while complex scales were detected, strongly depending on the Al content and temperature. Internal attack of AlN precipitates was also observed for Al-containing alloys at T> 700 °C. Highlights: ● Air-oxidation of NiCoCrAlx medium-entropy alloys was investigated at 600–900 °C. ● The oxidation kinetics of all the alloys followed the parabolic-rate law. ● The oxidation rates increased with increasing temperature and decreasing Al content. ● Complex scales formed on the alloys strongly depended on temperature and Al content.